Is Metagenomic Analysis an Effective Way to Analyze Fish Feeding Habits? A Case of the Yellowfin Sea Bream Acanthopagrus latus (Houttuyn) in Daya Bay - Pan, Wanni; Qin, Chuanxin; Zuo, Tao; Yu, Gang; Zhu, Wentao; Ma, Hongmei; Xi, Shigai (Frontiers in Marine Science, 2021)
Yellowfin seabream, Acanthopagrus latus, is one of the most important species in terms of stock enhancement in China. However, using metagenomic techniques to explore the feeding habits and stomach microbiome of yellowfin seabream is still rare. The objective of this work was to study the feeding habits and stomach microbiome of yellowfin sea bream from Daya Bay through metagenomic analysis of different weight classes (≤50 g, 50-100 g and >100 g). Whole-metagenome shotgun sequencing and morphological observation were used to investigate the stomach contents. The dietary composition and the community composition of the stomach microbiome of A. latus were examined. In this study, 153 species were detected in the eukaryotic composition of the stomach contents of yellowfin sea bream. At the species level, Mytilus edulis was the only species identified by both metagenomic analysis and morphological observation. The proportion of fish and bivalves was over 98%, but the diet changed little with body size. Larimichthys crocea, Scophthalmus maximus and Seriola dumerili were the most abundant species among all samples. In total, 285 species were identified in the stomach microbiome of yellowfin sea bream. Bacterium 2013Ark19i, bacterium 2013Arg42i and Acinetobacter baumannii, first reported in the stomach contents of yellowfin sea bream, were the most abundant species of the stomach microbiomes. There was no difference in the biodiversity of the stomach microbiomes among the different body sizes. Overall, the composition of the yellowfin sea bream diet mainly consists of fish and bivalves. The use of metagenomics techniques is a promising approach for assessing the feeding habits of yellowfin sea bream. The results derived from this study can provide important information for evaluating the feeding ecology of yellowfin sea bream in Daya Bay.